Memindai Posisi Strategis dan Alternatif Strategi Pengusaha Rotan Kota Pekanbaru - Nofrizal Nofrizal; Aznuryandi Aznuryandi; Afvan Aquino (Jurnal Manajemen dan Kewirausahaan, 2020)
The condition of rattan entrepreneurs in Pekanbaru city is already worrying, it is necessary to formulate an appropriate alternative strategy to save the rattan entrepreneurs so that they do not leave names. The research objectives are to analyze  the strategic position of the rattan entrepreneurs in Pekanbaru city  and to determine alternative strategies that could be used to nourish the rattan industry in Pekanbaru city. The research objects are rattan entrepreneurs with a population of 43 business units. Data collection techniques are through questionnaires, interviews and literature study. Data analysis uses  External Factor Evaluation (EFE), Internal Factor Evaluation (IFE),  SWOT-8K Matrix Analysis and QSPM Matrix Analysis. The results of this study are : 1) the conditions of the Pekanbaru city entrepreneurs in a very worrying position where the opportunity position is lower than the threat position, while the strength is in a lower position than the weakness, 2) Based on the SWOT-8K analysis, it shows the strategic position of the Pekanbaru city rattan entrepreneur is in the IIIA quadrant position, namely the sanitation strategy, and 3)  Based on the QSPM matrix analysis, the alternative strategy that can be used by rattan craftsmen in Pekanbaru city is aggressive sanitation strategy.https://doi.org/10.26905/jmdk.v8i2.4153